Assessing India-Afghanistan Strategic Partnership in the Twenty First Century - Bragta, Sanjeev Kumar (Technium Social Sciences Journal, 2025)
To comprehend the paradigm shift in the twenty first century, we need to understand the upsurge of India in the Indian Ocean Region (IOR) and the consecutive emergence of China in the post-cold war era. This has led to the geopolitical shift in Asia and particularly in the littoral waters of Indian Ocean. The classical geopolitics of governing the nation is still evident in the international relations. The processes of regionalism, multilateralism has replaced the geopolitical phenomenon in many parts of the world but geconomics in IOR is yet to replace the geopolitics. The traditional theory of geopolitics such as Alfred Thayer Mahan, Halford J. Mackinder, Nicholas Spykman seems to be prevalent in the South and Central as well as mid-west Asia. The role and response of India with Afghanistan encompass the historical evolution with multidimensional deliberated collaboration, characterising the geopolitical and economic foundations. The India-Afghanistan strategic partnership started evolving with the fall of Taliban since post-9/11 period. Not only this, New Delhi has emerged as major player in the reconstruction and rebuilding Kabul in the twenty first century. It is in this very context, the study purports to enquire into the India-Afghanistan relations in the present century with certain roadblocks.